PENYUSUNAN SAK EMKM BAGI SISWA YAYASAN PRIMA UNGGUL - Vidyarto Nugroho (PROSIDING SERINA, 2021)
The business sector can be classified into Micro, Small and Medium Enterprises (MSMEs) and Large (National/Multinational) and is one of the business sectors that participate in advancing the economy in Indonesia. In addition to playing a role in economic growth, MSMEs also play a role in employment. Each business sector has its own Accounting and Reporting Standards and its tax obligations. MSME financial reports are very simple and tend to ignore standard financial administration rules. The Indonesian Institute of Accountants has prepared SAK-EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) which came into effect as of January 1, 2018 to facilitate MSMEs in compiling company financial reports. This counseling aims to provide a more comprehensive insight for Prima Unggul Foundation students, who are trained to become entrepreneurs. It is hoped that they will be more stable and confident and can assist in better recording of the business/business that is being run, starting from making plans, knowing the rights and obligations as entrepreneurs and other technical matters in connection with their business accounting records. The activities  run smoothly and will be useful in adding insight to the Prima Unggul Foundation students.